Nitrate as an alternative electron acceptor destabilizes the mineral associated organic carbon in moisturized deep soil depths - Song, Wei; Hu, Chunsheng; Luo, Yu; Clough, Tim J.; Wrage-Mönnig, Nicole; Ge, Tida; Luo, Jiafa; Zhou, Shungui; Qin, Shuping (Frontiers in Microbiology, 2023)
Numerous studies have investigated the effects of nitrogen (N) addition on soil organic carbon (SOC) decomposition. However, most studies have focused on the shallow top soils < 0.2 m (surface soil), with a few studies also examining the deeper soil depths of 0.5-1.0 m (subsoil). Studies investigating the effects of N addition on SOC decomposition in soil > 1.0 m deep (deep soil) are rare. Here, we investigated the effects and the underlying mechanisms of nitrate addition on SOC stability in soil depths deeper than 1.0 m. The results showed that nitrate addition promoted deep soil respiration if the stoichiometric mole ratio of nitrate to O2 exceeded the threshold of 6:1, at which nitrate can be used as an alternative acceptor to O2 for microbial respiration. In addition, the mole ratio of the produced CO2 to N2O was 2.57:1, which is close to the theoretical ratio of 2:1 expected when nitrate is used as an electron acceptor for microbial respiration. These results demonstrated that nitrate, as an alternative acceptor to O2, promoted microbial carbon decomposition in deep soil. Furthermore, our results showed that nitrate addition increased the abundance of SOC decomposers and the expressions of their functional genes, and concurrently decreased MAOC, and the ratio of MAOC/SOC decreased from 20% before incubation to 4% at the end of incubation. Thus, nitrate can destabilize the MAOC in deep soils by stimulating microbial utilization of MAOC. Our results imply a new mechanism on how above-ground anthropogenic N inputs affect MAOC stability in deep soil. Mitigation of nitrate leaching is expected to benefit the conservation of MAOC in deep soil depths.